The Utilizing of Tongue Twister Media for English Speaking Activity of Management Students in School of Management - Elda Yulia Ryandini; Anis Fitriyasari (Institut Agama Islam Negeri Palopo, 2023)
The ability of using English is important and is needed nowadays in many aspects. Everyone is supposed to be able to speak English for communication. The problem happens in non-English students who learn English for specific purpose. They do not feel confident to perform speaking due to they are very rare practicing English previously that causes some problems in pronunciation and mastery vocabulary. Therefore, this study is aimed to know the management students’ pronunciation of English words using tongue twister media and to probe the management students’ perception in speaking English activity. This research applies a qualitative approach with 24 Management major students from one class who mostly work and enroll online and offline English class. The instrument used are field note observation, questionnaires, and recorder. The findings show that most management students found speaking problems in pronouncing the sounds of /θ/, /ð/, /ʃ/ and /ai/. Although they were not confident in speaking English for the improper pronunciation, they were still trying to learn English well. They expressed that the utilize of tongue twister media in speaking activity is helpful, fun and challenging to pronounce and listen to the good pronunciations.